Analysis of meniscal hoop strain in porcine knees - Low, Kelvin Yong Cai (Nanyang Technological University, 2020)
Two menisci (lateral and medial) can be found in the human knee, located between the femur (thighbone) and tibia (shinbone). The femur and tibia are roped together by two cruciate and collateral ligaments each. The meniscus is a crescent-shaped cartilage responsible for pivotal movements in a human knee. Specifically, it supplements the joint with stability, congruity, and lubrication, while also serving as a shock absorbing mechanism and transmit load between the femoral and tibia condyles. As such, the unique composition and anatomic attachments allow the meniscus to be recognised as an important component in the biomechanics of the knee joint. However, the meniscus is vulnerable to internal impact that can potentially lead to injuries like meniscal tear. The study aims to determine the change in strain distribution of the menisci when either the medial or lateral meniscus is cut radially by 50%. Six fresh porcine specimens were used as cadaveric knee substitutes. A 50% radial cut, at the middle third equidistant to the two ends of the meniscus body, was created on three medial menisci and three lateral menisci of different specimen. Instron 5566 machine was used to induce 700 N to 1000 N force on the knee joint at full extension (30º), and Differential Voltage Reluctance Transducer (DVRT) was used to measure the hoop strain during intact and after the respective radial cut. The mean strain ranged from 0% to 4% with highest strain demonstrated at the posteromedial region. The slope of the mean strain graph was non-linear with respect to the induced load, suggested that there was no proportionality. Strain increment was consistently noted at the respective region of meniscus with radial cut, plausibly due to the increase in stress (force over area) caused by area reduction from the radial cut. However, the medial meniscus sustained strain increment when a radial cut was performed at either medial or lateral meniscus, showing its primary role in shouldering the load transmission after a radial tear.